Fast microflow kinetics and acid catalyst deactivation in glucose conversion to 5-hydroxymethylfurfural. Issue 1 (9th November 2020) - Chen, Tai-Ying; Cheng, Ziwei; Desir, Pierre; Saha, Basudeb; Vlachos, Dionisios G.
Abstract : Continuous flow microreactors operating at short residence times and high temperatures can give high HMF productivity and contribute to process intensification of biorefineries. Abstract : 5-Hydroxymethyl furfural (HMF) is an important platform chemical because it can be upgraded to various drop-in and performance-advantaged products. The cascade reaction of HMF production from glucose over a Lewis acid (CrCl3 ) and a Brønsted acid (HCl) catalyst in aqueous media is investigated in a microreactor at short residence times and high temperatures. We study the formation of various chromium species using UV-visible spectrophotometry and elucidate the Cr(iii ) speciation. The catalyst reactivity increases sharply at short residence times, and then drops at long times. This indicates that the catalyst treatment plays a vital role in getting optimal reactivity, and recording the catalyst history is necessary. We develop a kinetic model to describe the catalyst speciation as well as the Lewis and Brønsted acid-catalyzed reaction kinetics using a hierarchical approach. The model is in good agreement with experiments. We demonstrate the benefits of tandem Lewis-external added Brønsted acid catalysis in processing time, productivity, and catalyst stability. We apply this model to optimize the HMF yield and obtain ∼36% yield at 200 °C in 7 min and report the highest productivity of ∼15% yield per min, demonstrating the opportunity of reaching high productivity at short residence times.